Implementasi Kebijakan Bendungan di Kabupaten Kampar - Silfahira, Nindiyani; Yuliani, Febri (Public Policy, 2021)
The purpose of this study was to determine the implementation of thedam policy (study on the impact of the existence of floating net cages). The method used in this research is a qualitative method using descriptive case study methods with data collection techniques through interviews and documentation, using the theory of policy implementation from Van Metter and Van Horn. The results showed that the implementation of the dam control policy was carried out by applying measures and policy objectives, resources, characteristics of the executing agent, attitudes / tendencies of implementing agents, communication, social, economic and political environment. Then there are inhibiting factors in the implementation of dam control policies (a case study of the impact of the existence of floating net cages) in Kampar Regency, namely the increase in river water discharge which threatens the safety of floating net cages, the anticipation of the cage community is still very minimal in the face of high water discharge during the rainy season, depth. The unstable water greatly affects the floating net cage system, there is still a lack of communication between the Plta Koto Panjang and the floating net cage community, the floating net cage community has experienced a drastic economic decline due to the release of dam water during the rainy season, mass fish die.